2017
DOI: 10.1002/syn.22014
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of synaptic caspase substrates

Abstract: The dismantling and elimination of excess neurons and their connections (pruning) is essential for brain development and may be aberrantly reactivated in some neurodegenerative diseases. Growing evidence implicates caspase-mediated apoptotic and nonapoptotic cascades in the dysfunction and death of neurons in neurodegenerative disorders such as Alzheimer's, Parkinson, and Huntington's diseases. It is the cleaved caspase substrates that are the effectors of synapse elimination. However, their identities, specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Interestingly our interactome analysis showed that endogenous GPRIN1 specifically interacts with caspase-3 in primary neurons ( Fig. S3G ) as previously reported at synaptic level (Victor et al, 2018). In line with these findings we showed that GPRIN1 interacted with caspase3 in SHSY-5S neuroblastoma cell lines and AMPA stimulation likely increased this interaction ( Fig.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Interestingly our interactome analysis showed that endogenous GPRIN1 specifically interacts with caspase-3 in primary neurons ( Fig. S3G ) as previously reported at synaptic level (Victor et al, 2018). In line with these findings we showed that GPRIN1 interacted with caspase3 in SHSY-5S neuroblastoma cell lines and AMPA stimulation likely increased this interaction ( Fig.…”
Section: Resultssupporting
confidence: 87%
“…In particular, a specific function has been proposed for GPRIN1 as a scaffold protein capable of driving the interaction between α4 nAChRs and Gαi in T cells (Nordman et al, 2014) and, recently, of mediating the anti-inflammatory properties of α7 nAChRs/Gαq signaling in microglia cells (King et al, 2017). Finally a recent proteomic study identified GPRIN1 as a novel synaptic substrate for caspase 3-dependent proteolytic cleavage, the major early event in synapse loss and neurodegeneration (Victor et al, 2018). Considering our findings showed increased level of activated caspase 3 in neurons lacking GPRIN1, further investigation needs to be done to determine whether in healthy neurons GPRIN1 inhibit caspase 3 activity in neurons by sequestering it and whether GPRIN1 might be itself a proteolytic substrate of caspase 3.…”
Section: Discussionmentioning
confidence: 99%
“…Official gene symbols of protein sets were submitted to the online tool Draw Venn Diagram (Bioinformatics and Evolutionary Genomics, Ghent University 1 ) to obtain the numbers of unique proteins found in each set and their overlaps. This site was used to generate Figure 3 comparing ABC3 substrates, the brainstem proteome, and previously identified caspase-3 substrates (Lüthi and Martin, 2007;Rawlings et al, 2010;Crawford et al, 2013;Victor et al, 2018). For all other Venn diagrams, the numbers in set overlap from Draw Venn Diagram were used to create Venn diagrams with proportionally accurate areas using the Euler package on R.…”
Section: Protein Set Comparisonmentioning
confidence: 99%
“…Auditory Brainstem Caspase-3 Activity Cleaves Both Novel and Known Substrates, Especially Known Substrates Observed in Non-apoptotic Contexts Next, we investigated whether our ABC3 substrates have been previously reported as caspase-3 substrates and whether they are associated with apoptotic or non-apoptotic caspase activity. We consulted four sources of known caspase-3 substrates: MEROPS (Rawlings et al, 2010), CASBAH (Lüthi and Martin, 2007), DegraBase (Crawford et al, 2013), and Victor et al, 2018. We used a hypergeometric test to calculate the probability of obtaining the observed number of proteins that were caspase-3 substrates both in the above databases and in our ABC3 dataset, assuming each is randomly selected from a brainstem proteome of 5,653 proteins containing 288 caspase-3 substrates. Nearly one third (91) of our 288 ABC3 substrates were present in at least one of the four datasets (p = 2.45 × 10 −10 ), suggesting that caspase-3 cleaves many of the same proteins in the developing auditory brainstem as in other conditions (Figure 3, Table 2, Supplementary Data 2).…”
Section: Abc3 Substrates Were Most Likely Cleaved By Caspase-3 Not Omentioning
confidence: 99%
See 1 more Smart Citation